High-level mosaicism for 45,X in 45,X/46,XX at amniocentesis in a pregnancy with a favorable outcome and postnatal progressive decrease of the 45,X cell line - Chih-Ping Chen; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Chen-Chi Lee; Yun-Yi Chen; Wayseen Wang (Elsevier, 2022)
Objective: We present prenatal diagnosis of high-level mosaicism for 45,X in 45,X/46,XX at amniocentesis in a pregnancy with a favorable outcome and postnatal progressive decrease of the 45,X cell line. Case report: A 32-year-old, gravida 2, para 1, woman underwent amniocentesis at 17 weeks of gestation because of the abnormal first-trimester maternal serum screening result indicating a 1/34 risk for Down syndrome. Amniocentesis revealed a karyotype of 45,X[27]/46,XX[15]. Simultaneous array comparative genomic hybridization (aCGH) on uncultured amniocytes revealed 12% mosaicism for monosomy X. Prenatal ultrasound was normal. The pregnancy was carried to term, and a 2780-g phenotypically normal female baby was delivered. The cord blood had a karyotype of 45,X[12]/46,XX[28]. At age one month, the peripheral blood had a karyotype of 45,X[13]/46,XX[27]. Interphase fluorescence in situ hybridization (FISH) analysis on the buccal mucosal cells revealed 2% (2/102 cells) mosaicism for monosomy X, compared with 1% (1/100 cells) in the normal control. When follow-up at age one year, she was doing well with normal physical and psychomotor development. Her body weight was 9.9 Kg (50th - 85th centile), and her body height was 75 cm (50th - 85th centile). The peripheral blood had a karyotype of 45,X[4]/46,XY[36]. Conclusion: High-level mosaicism for 45,X in 45,X/46,XX at amniocentesis can be associated with a favorable outcome and postnatal progressive decrease of the 45,X cell line.